Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M207 - Hummels, Rebecca; Schumacher, Mia; Wölfl, Anne-Cathrin (PANGAEA, 2025)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M207 using a 12kHz Kongsberg EM 122 multibeam echosounder. The expedition took place during 2025-01-05 – 2025-02-11 from Belem (Brazil) to Mindelo (Cape Verde) in the Central Atlantic. The major aims of M207 are to investigate the variability of the western boundary current circulation off South America and to contribute to the assessment of the variability of the Atlantic Meridional Overturning Circulation (AMOC) at 11S. Data were recorded within the EEZ of Brazil as well as outside EEZs. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by GEOMAR Helmholtz Centre for Ocean Research, provision of the data is supported by the DAM Project Underway Research Data and published according to the FAIR principles.
Keywords: Bathymetry; Multibeam Echosounder